871. Symptomatic Respiratory Syncytial Virus and Adenovirus Upper Respiratory Tract Infections Increase the Risk of Invasive Aspergillosis After Allogeneic Hematopoietic Cell Transplantation. (26th November 2018) - Ogimi, Chikara; Campbell, Angela P; Xie, Hu; Fisher, Cynthia; Kuypers, Jane; Jerome, Keith; Chien, Jason; Callais, Cheryl; Waghmare, Alpana; Cheng, Guang-Shing; Leisenring, Wendy; Englund, Janet; et al.
Abstract: Background: Invasive aspergillosis (IA) is a serious infectious complication following hematopoietic cell transplantation (HCT). Few studies have reported respiratory viral infections (RVIs) as a risk factor for developing IA, and data regarding specific viruses is sparse. We examined whether specific respiratory viruses were associated with increased risk of developing IA post-HCT. Methods: In a longitudinal surveillance study of RVIs among allogeneic HCT recipients conducted 2005–2010, weekly post-HCT nasal washes were collected through day 100, then every 3 months, and whenever respiratory symptoms occurred through 1 year post-HCT. Nasal and bronchoalveolar lavage (BAL) samples were tested by multiplex PCR for respiratory syncytial virus (RSV), parainfluenza viruses (PIV)1–4, influenza A/B, human metapneumovirus, adenovirus (ADV), and human rhinoviruses, and coronaviruses. Only respiratory virus detections with symptoms were counted as RVI. Separate Cox proportional hazards models were used to examine adjusted associations between each RVI and the development of first proven/probable IA by 1-year post-HCT. Results: Among 437 patients who survived >28 days following HCT, 39 patients developed IA by 1-year post-HCT (median 87 days, range 5–283). After adjusting for age at HCT, neutropenia, high-grade CMV viremia, and HLA status (matched related vs. others) or severe acute graft-versus-host disease (GVHD Grade 0–2 vs. 3–4), RSV and ADV upper respiratory tract infections (URTI) were associated with increased risk of developing IA (figure). Detection of any respiratory virus in the BAL was associated with IA ( P < 0.001). Conclusion: RSV and ADV URTI are significant risk factors for development of IA post-HCT; the association between PIV URTI and development of IA approached statistical significance. Viral lower respiratory tract infection was associated with IA. Our data provide a rationale to assess IA as an endpoint in preventive studies of novel agents for respiratory viruses and further emphasize the importance of effective infection prevention practices for RVIs after HCT. Disclosures: J. Chien, Gilead Sciences, Inc.: Employee and Shareholder, Salary and stocks. A. Waghmare, Ablynx: Investigator, Research support. J. Englund, Gilead: Consultant and Investigator, Consulting fee and Research support. Novavax: Investigator, Research support. GlaxoSmithKline: Investigator, Research support. Alios: Investigator, Research support. MedImmune: Investigator, Research support. M. Boeckh, Asun Biopharma: Consultant and Investigator, Consulting fee and Research support. Gilead Sciences: Consultant and Investigator, Consulting fee and Research support. Chimerix Inc.: Consultant and Investigator, Consulting fee and Research support. Humabs: Consultant, Consulting fee. GSK: Investigator, Research support.